Finnish parents’ perceptions of death following the traumatic death of a child - Nur Atikah Mohamed Hussin; Terhi Talvitie; Eetu Laitinen; Anna Liisa Aho (BMC Psychology)
Abstract Children are expected to outlive and live longer than their parents. However, the traumatic death of a child challenges parents’ understanding of life and death. If parents are unable to form their own perceptions of death after such a loss, it can hinder their ability to cope and adjust. This study aims to explore parents’ perceptions of death following the traumatic death of a child. To recruit participants, an online advertisement was posted on the websites of Finnish bereavement organizations, their member mailing lists, and closed discussion groups. The study consisted of two phases. In the initial phase, 66 parents responded to open-ended questions via the LimeSurvey platform. Subsequently, 17 parents were interviewed in-depth over the phone. The findings were analyzed using thematic analysis. The perceptions of parents who had experienced the traumatic death of a child included death is universal, awakening or preparing for their own death, reunion in death, death and spiritual growth, and death is unjustified. These findings highlight the importance of providing support to parents following the traumatic death of a child, which can help them reconstruct perceptions of death and better adapt to their loss.